MATERNOFETAL INTERACTION AND MODULATION IN CREATING A NEW POPULATION: A REVIEW OF CURRENT EVIDENCE ON THE RELATIONSHIP BETWEEN FETAL NUTRITION AND THE DEVELOPMENT OF CHRONIC DISEASES LATER IN LIFE - Novaković, Ivana; Todorović, Jovana; Dugalić, Stefan; Gojnić, Miroslava (Srpski medicinski časopis Lekarske komore, 2023)
The concept of fetal programming has found its place in science and keeps lighting the way to better understanding of fetal life and its impact on postnatal and adult life. Its capacity is much wider than a common recognition of the fact that different disorders in pregnancy impact fetal health, and these capacities keep being confirmed by various observational studies and experimental models. Another fact that makes fetal programming even harder to confirm and accept is the long period between the stimulus and its consequences, as well as various factors that can change and influence this period of one’s lifetime. Nevertheless, different hypotheses are present, concerning suboptimal fetal health and nutrition and their contribution to the development of chronic diseases during one’s lifetime - inadequate nutrition during intrauterine period and early childhood can permanently change one’s physiology and metabolism, which contributes to a possible development of chronic diseases (hypertension, coronary artery disease, stroke, diabetes, etc.). The aim of this paper is to review current evidence on the relationship between fetal nutrition and the risk of chronic diseases later in life. A detailed review of current literature and the analysis of various studies aimed at following neonates to their adulthood in order to determine the significance of fetal programming. An association between suboptimal fetal growth and a higher risk of metabolic syndrome, insulin resistance, diabetes type 2, and hypertension, has been proven by the studies conducted within different populations and age groups. Based on the evidence presented in this paper, it can be concluded that fetal programming has been recognized as significant and is on the way to becoming the third contributing factor in the development of chronic diseases during one’s lifetime, along with a genetic predisposition and lifestyle.